2022
DOI: 10.12997/jla.2022.11.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Attainment of Lipid Targets Following Coronary Artery Bypass Graft Surgery: Can We Do Better?

Abstract: Objective Patients undergoing coronary artery bypass graft (CABG) surgery remain at high cardiovascular risk; however, few studies have evaluated lipid management and attainment of lipid targets in these patients. We investigated the proportion of CABG surgery patients who attained low-density lipoprotein cholesterol (LDL-C) and non-high-density lipoprotein cholesterol (HDL-C) targets. Methods Data were retrospectively obtained from patients undergoing CABG surgery at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Similarly, in the International ChoLesterol management Practice study (ICLPS), a cross‐sectional observational study conducted in 18 countries, including the Gulf region, only 32.1% of the very high‐risk patients achieved their LDL‐C goal (1.80 mmol/L). 23 Moreover, in 2 single‐center observational studies, achievement of the LDL‐C treatment goal (1.40 mmol/L) in the extremely high‐risk patient group was noted in only 24.4% 14 and 29% 15 of those treated by lipid‐lowering agents. Furthermore, in a patient‐level pooled analysis of 3 randomized clinical trials undertaken by Farkouh et al, 22 including 4050 consecutive patients, the proportion of patients who had attained the LDL‐C goal (1.80 mmol/L) was only 35%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the International ChoLesterol management Practice study (ICLPS), a cross‐sectional observational study conducted in 18 countries, including the Gulf region, only 32.1% of the very high‐risk patients achieved their LDL‐C goal (1.80 mmol/L). 23 Moreover, in 2 single‐center observational studies, achievement of the LDL‐C treatment goal (1.40 mmol/L) in the extremely high‐risk patient group was noted in only 24.4% 14 and 29% 15 of those treated by lipid‐lowering agents. Furthermore, in a patient‐level pooled analysis of 3 randomized clinical trials undertaken by Farkouh et al, 22 including 4050 consecutive patients, the proportion of patients who had attained the LDL‐C goal (1.80 mmol/L) was only 35%.…”
Section: Discussionmentioning
confidence: 99%
“… 11 However, recent studies showed that a significant proportion of patients are undertreated and have LDL‐C levels exceeding the target, suggesting that the effect of LDL‐C on the prognosis of patients undergoing CABG was still disregarded or underestimated to some extent. 14 , 15 , 16 , 18 Generally, patients undergoing CABG have a more severe atherosclerotic disease, which may be the reason for their increased risk, but this also illustrates the greater benefits they experience in response to further LDL‐C reduction. Aggressive lipid‐lowering therapy is attractive to avoid post‐CABG saphenous vein graft disease and may be effective to maintain long‐term graft patency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from 1-year follow-up of a Middle-Eastern cohort showed that 59.3% and 29% of CABG patients attained LDL-C targets of <1.8 mmol/L and 1.4 mmol/L, respectively (31). A most recent study from Australia with a median follow-up of 483 days reported that the attainment of LDL-C target <1.8 mmol/L was 47.7%and that of Frontiers in Cardiovascular Medicine 06 frontiersin.org <1.4 mmol/L was 24.4% (32). Another retrospective analysis of 1,230 CABG patients with a median follow-up period of 101 months showed that 44% of the patients reached the target of <1.8 mmol/L (33).…”
Section: Discussionmentioning
confidence: 99%